Pengembangan Instrumen Kognitif Fisika Siswa SMP - Mustika Wati; Saiyidah Mahtari (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2017)
[Title: Development of Physics Cognitive Instruments Of Junior High School Students] This study aims to develop cognitive instruments on energy and business materials, simple aircraft and light quality. The specific purpose of this study is to describe: (1) the validity of cognitive instruments seen from Outfit MNSQ, ZSTD, and Pt Measure Corr; (2) the reliability of cognitive instruments seen from the values of individual separation, grain separation, and Cronbach Alpha; (3) the degree of difficulty seen from the logit value in the measurement column; This development research refers to the development model of Borg and Gall with the subject of research of 200 students of class VIII originating from several SMPN in Banjarmasin. Instrument collecting data in the form of validation and cognitive instruments. Data analysis techniques are descriptive and quantitative. The results showed: (1) five items of description on light material, nine items about the description of simple plane materials and nine items about the description of energy materials and businesses that are categorized as valid; (2) reliability of cognitive instruments seen from individual separation values, grain separation values, and Cronbach Alpha values are categorized as very reliable; (3) the difficulty level of questions seen from the logit of categorized is very difficult, difficult, easy, and very easy.